Endobronchial Infection and Bacterial Lymphadenitis by Gemella morbillorum Leading to Airway Perforation and a Bronchopleural Fistula - Kaitlin N. DePrez; John Ferguson (Case Reports in Pulmonology)
Conclusion: In cases of severe mediastinal adenopathy in a young patient, bacterial lymphadenitis should be considered in the differential diagnosis with lymphoma, germ cell tumor, granulomatosis with polyangiitis, sarcoidosis, histoplasmosis, and inflammatory myofibroblastic tumor.